2020
DOI: 10.1007/jhep01(2020)124
|View full text |Cite
|
Sign up to set email alerts
|

The dynamical diquark model: fine structure and isospin

Abstract: We incorporate fine-structure corrections into the dynamical diquark model of multiquark exotic hadrons. These improvements include effects due to finite diquark size, spin-spin couplings within the diquarks, and most significantly, isospin-dependent couplings in the form of pionlike exchanges expected to occur between the light quarks within the diquarks. Using a simplified two-parameter interaction Hamiltonian, we obtain fits in which the isoscalar J P C = 1 ++ state-identified as the X(3872)-appears natural… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 44 publications
2
55
0
Order By: Relevance
“…However, some support in favor of a flavor-spin interaction in exotics is given by Ref. [37]. Although restricted to tetraquarks described in a diquark basis, it has been shown that the mass difference observed in some charmed tetraquarks can be explained by an isospin dependent interaction, which is an SU(2) flavor-spin interaction.…”
Section: Strong Decay Widthsmentioning
confidence: 99%
“…However, some support in favor of a flavor-spin interaction in exotics is given by Ref. [37]. Although restricted to tetraquarks described in a diquark basis, it has been shown that the mass difference observed in some charmed tetraquarks can be explained by an isospin dependent interaction, which is an SU(2) flavor-spin interaction.…”
Section: Strong Decay Widthsmentioning
confidence: 99%
“…While it is possible to fit the 3 constants M 0 , κ qQ , V 0 using nothing but the 3 PDG-averaged mass eigenvalues of X(3872), Z c (3900), and Z c (4020), and indeed such a restrictive fit gives results virtually identical to those in Ref. [24]:…”
Section: A Operators Appearing For 1s and 1pmentioning
confidence: 83%
“…We inferred in Ref. [24] that the isospin-dependent couplings, at least in the S wave, appear to see only the light quarks, and do not view the diquarks as pointlike constituents. Indeed, one of the major thrusts of Ref.…”
Section: A Operators Appearing For 1s and 1pmentioning
confidence: 93%
See 2 more Smart Citations